Head-up Position did not Correlated with the Recovery Time of Lower Extremity Motor Function in Spinal Anesthesia Patiens - Arif, Taufan; Hamarno, Rudi; Bharata, Bisma Surya; Bachtiar, Arief (STIKes Patria Husada Blitar, 2025)
Patients who are delayed in recovery after spinal anesthesia will be transferred to the post anesthesia care unit (PACU) which can lead to increased service costs and patient dissatisfaction. Lower extremity motor function recovery time after spinal anesthesia is the time it takes for patients to be able to move from the recovery room to the patient's original room. The purpose of this study was to determine the correlation of Head-up position to the recovery time of lower extremity motor function in spinal anesthesia patients in the recovery room. The design of the study was correlation with a “cross-sectional” approach. The population was post-spinal anesthesia patients in the recovery room who meet the criteria. The study used